(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Concrete is the most widely construction material in the world due its easy formation and availability of raw materials. The disadvantage of its use was cement since it responsible of most CO2 emissions in world. Besides that, due to rapid publication growth, the waste materials generated by humans, such as plastic, glass, and non-biodegradable materials, harm the environment, so most research has involved incorporating waste materials in concrete to create an eco-friendly concrete. In this research, some studies that replaced cement with silica fume, palm ash, and fly ash, sand with glass powder and PET, gravel with crushed concrete and rubber were reviewed.